Microsurgery of chronic laryngeal diseases using fiber optic lasers. A review - Aleksandr A. Krivopalov; Polina A. Shamkina; Alexandra I. Glushchenko (Consilium Medicum, 2023)
Background. The treatment of chronic diseases of the larynx is an urgent issue. Chronic larynx masses account for up to 5570% of the upper respiratory tract proliferative diseases. The incidence of vocal apparatus disorders is stable due to increased load on the vocal apparatus, neuro-emotional stress, non-compliance with voice hygiene (smoking, alcohol consumption), nasal and pharyngeal inflammatory diseases, sensibilization, and gastrointestinal disorders. Dysphonia, voice timbre changes, and vocal fatigue are presented in 712% of otorhinolaryngologist patients. Delayed treatment of chronic larynx diseases can lead to upper respiratory obstruction, reduced exercise and self-care tolerance, and disablement in people with voice and speech professions.